Hubungan Pengetahuan Ibu Dengan Penanganan Pasca Imunisasi Dpt- Hb-Hib Pada Bayi Baduta Diwilayah Kerja Puskesmas Lingkar Timur Kota Bengkulu Tahun 2025 - Olpi Merlia; Delta Aprianti; Fitriana Fitriana (Jurnal Multidisiplin Dehasen (MUDE), 2026)
DPT-HB-Hib immunization is an important preventive measure in reducing morbidity and mortality in infants under five. However, adverse events following immunization (KIPI) often raise concerns among mothers, especially when knowledge regarding post-immunization care is still limited. This study aims to analyze the relationship between maternal knowledge and post-immunization care for DPT-HB-Hib infants under five in the working area of the Lingkar Timur Community Health Center in Bengkulu City in 2025. The research method used is quantitative with a descriptive analytical design through a cross-sectional approach. Sampling was carried out using a purposive sampling technique on 80 mothers with infants under five. Data were collected using a structured questionnaire and analyzed univariately and bivariately using the Chi-Square test. The results showed that most mothers had a good level of knowledge and carried out good post-immunization care. Statistical tests showed a significant relationship between maternal knowledge and post-immunization care for DPT-HB-Hib. This study concluded that the better the mother's knowledge, the more appropriate the post-immunization care they carried out.